Immunohistochemical expression of pi class glutathione S-transferase in the basal cell layer of benign prostate tissue following chronic treatment with finasteride. Issue 5 (1st May 1999) - Montironi, R; Mazzucchelli, R; Pomante, R; Thompson, D; Duval da Silva, V; Vaught, L; Bartels, P H
Abstract : BACKGROUND: Glutathione S-transferases (GST) may prevent carcinogenesis through inactivation of reactive electrophiles by conjugation to reduced glutathione. Treatment directed at the induction or preservation of GST-pi expression in normal epithelium could have a profound impact on the prevention of prostate neoplasia. Finasteride, a 5-alpha-reductase inhibitor, is used as a chemopreventive agent because it blocks the conversion of testosterone to its byproduct which promotes prostate tumour growth. OBJECTIVE: To investigate GST-pi expression immunohistochemically in benign prostate tissue from untreated patients and from patients chronically treated with finasteride. MATERIALS: Immunostaining with anti-GST-pi antibody was performed on 10 (cysto-) prostatectomy, eight simple prostatectomy, and three transurethral prostatectomy specimens. The first set of 10 prostates was from untreated patients operated on for bladder cancer. The other cases were from patients with benign prostatic hyperplasia and chronically treated with finasteride. None of the specimens in either group showed prostatic cancer, prostatic intraepithelial neoplasia, urothelial carcinoma, or chronic prostatitis. Specimens were evaluated for the presence, intensity, and distribution of immunostaining. RESULTS: Diffuse cytoplasmic immunostaining was observed in the basal cell layer of the untreated specimens. Some variability in the expression of GST-pi was seen within each zone and also between the prostate zones. Only a minority of the secretory cells was stained weakly, mainly in the subnuclear region of the cells facing an uninterrupted basal cell layer. Staining was more homogeneously diffuse in the cytoplasm of the luminal cells facing the basement membrane directly. In the benign epithelium of the finasteride treated specimens the circumferential staining of the basal cells appeared to be more continuous than in the untreated cases, the gaps in the stained basal cell layer being fewer, shorter, or even absent in some ducts and acini. There was no variability in the intensity of staining of the basal cell layer, all the cells being intensely stained in a uniform way. The intensity of staining of the secretory cells was not influenced by finasteride treatment. CONCLUSIONS: Following chronic treatment with finasteride the immunohistochemical expression of pi class glutathione S-transferase in the benign prostate ducts and acini is upregulated in relation to an expanded basal cell layer. This could indicate that finasteride acts as a GST-pi inducer.